The Need for Systems Tools in the Practice of Clinical Medicine. Issue 1 (30th March 2017) - Khayal, Inas S.; Farid, Amro M.
ABSTRACT: Humanity is currently facing an unprecedented chronic disease burden. Healthcare needs have significantly shifted from treating acute to treating chronic conditions. Chronic diseases tend to involve multiple factors with complex interactions between them evidenced by the continually growing medical knowledge base. The health profession requires the ability to manage this rapidly deepening knowledge base to assimilate the lessons from research and clinical care experience by systematically capturing, assessing, and translating it into the highest level of reliable care. A more systems approach to practicing medicine exists and is referred to as functional medicine. It takes into account the many subsystems in the human body and their many interactions. Although the science behind treating the patient as a system exists, the application of systems tools and techniques have not been utilized. It is only natural to begin to formalize the systems thinking using the established tools from the systems engineering field. Specifically, this paper presents the need for systems tools in the practice of clinical medicine and includes an example application of model‐based systems engineering to clinical medicine.